Analisis Yuridis Putusan Hakim Dalam Perkara Perdata Terhadap Penjatuhan Uang Paksa Dalam Gugatan Wanprestasi (Studi Putusan Nomor: 80/PDT/2024/PT.Tjk) - Asmara, Bunga Dewi; Rusli, Tami; Ramadan, Suta (CV. Rayyan Dwi Bharata, 2025)
Civil case resolution in Indonesia often involves conflicts between parties with different legal interests, where the court is the main means to achieve justice. This study aims to analyze the judge's decision regarding the imposition of forced money (dwangsom) in a breach of contract lawsuit, focusing on the Decision of the Tanjung Karang District Court Number 80/PDT/2024/PT.Tjk. The method used is qualitative research with a normative and empirical legal approach, collecting data from literature studies and interviews with judges and advocates. The results of the study indicate that the judge's considerations in imposing forced money are influenced by the principle of an independent trial and the interpretation of the relevance of the demand for forced money as a form of punishment. This study is expected to provide solutions to improve consistency and fairness in judges' decisions, as well as create legal certainty in resolving civil disputes.